Quantitative Concepts for Management / Decision Making Without Algorithms: Third Edition - Eppen Gary D; Gould F.J; Schmidt Charles (Prentice Hall, 1988)
Preface, An Introduction to Models, Data and Models, Constrained Optimization Models, Formulation of Constrained Optimization Models, Formulation of Constrained Optimization Models, Geometric Representation of the Linear Programming Model, Linear Programs: Computer Analysis and Interpreting Sensitivity Output, Special LP Topics: Duality V(b) and V(c), Two Case Studies at PROTRAC Based on Computer Analysis of the Model, Multiple Objectives and Goal Programming, Integer Programming and Network Models and Quadratic Programming, Project Management: PERT and CPM, Calculus-Based Optimization and an Introduction to Nonlinear Programming, Decision Theory and Decision Trees, Inventory Control with Known Demand, Inventory Models with Probabilistic Demand, Forecasting, Simulation Models, Queuing Models, Dynamic Programming, Appendices, The Simple Algorithm, Index.
Preface, An Introduction to Models, Data and Models, Constrained Optimization Models, Formulation of Constrained Optimization Models, Formulation of Constrained Optimization Models, Geometric Representation of the Linear Programming Model, Linear Programs: Computer Analysis and Interpreting Sensitivity Output, Special LP Topics: Duality V(b) and V(c), Two Case Studies at PROTRAC Based on Computer Analysis of the Model, Multiple Objectives and Goal Programming, Integer Programming and Network Models and Quadratic Programming, Project Management: PERT and CPM, Calculus-Based Optimization and an Introduction to Nonlinear Programming, Decision Theory and Decision Trees, Inventory Control with Known Demand, Inventory Models with Probabilistic Demand, Forecasting, Simulation Models, Queuing Models, Dynamic Programming, Appendices, The Simple Algorithm, Index.